A high-stability manganese-doped fluorosilicate potassium graphene quantum dot coated red fluorescent powder, a preparation method thereof and an application thereof
Patent Information
- Application Number
- CN202610776762.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-01
- Publication Date
- 2026-10-23
AI Technical Summary
然而KSF:Mn4+在实际应用中存在两个关键问题:(1)耐湿性差,Mn4+在潮湿环境中易水解生成MnO2或Mn2+,导致发光猝灭;(2)热稳定性不足,高温下荧光热猝灭显著,难以满足高功率LED或Micro LED对热稳定性的要求
1. 本发明通过Na+共掺杂、抗坏血酸表面还原钝化、GFQDs-GA共价交联网络三层梯度防护结构,从根源上解决了氟化物红色荧光粉耐湿性差和热稳定性不足的共性难题。内层Na+共掺杂使晶格收缩、晶体场增强,显著提升热稳定性;中层经抗坏血酸原位还原形成的贫Mn4+钝化层,降低了表面高活性Mn4+的浓度,切断了水分子侵蚀的起始点;外层由氨基/含氟双功能化石墨烯量子点经戊二醛席夫碱交联而成的三维网络,不仅形成致密的物理防水屏障,而且通过共价键将GFQDs牢固锚定于荧光粉表面,避免了传统物理吸附易脱落的缺陷。三层之间功能互补、逐级防护,85℃/85% RH老化1000h后发光强度保持率保持超过90%,水浸480min后保持率高于86%,综合性能优越。
Smart Images

Figure CN122959020A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of luminescent materials technology, specifically relating to a highly stable manganese-doped potassium fluorosilicate graphene quantum dot-coated red phosphor, its preparation method, and its application. Background Technology
[0002] Mn 4+ Doped fluoride red phosphors (such as K2SiF6:Mn) 4+ KSF (KnS) is widely used in wide color gamut displays and lighting due to its narrow-band emission (~630nm), high color purity, and good matching with blue LED chips. However, KSF:Mn 4+ Two key problems exist in practical applications: (1) poor moisture resistance, Mn 4+ It readily hydrolyzes in humid environments to form MnO2 or Mn. 2+ (1) It leads to luminescence quenching; (2) It has insufficient thermal stability, and the fluorescence quenching is significant at high temperatures, making it difficult to meet the thermal stability requirements of high-power LEDs or Micro LEDs.
[0003] To address the aforementioned technical problems, existing technologies have developed various modification strategies: (1) Ion exchange assisted surface passivation (IASP): Mn-depleted surface passivation is formed on the KSF surface by using solutions such as NH4F / HCl. 4+ The shell layer improves water resistance, but this method requires strict control of anhydrous or low-water conditions, has a narrow process window, and results in poor batch consistency.
[0004] (2) Na + Co-doping: using Na + Partially replaces K + It can improve the probability of radiative transitions and thermal stability, but Na alone... + Doping has limited effect on improving moisture resistance.
[0005] (3) Graphene quantum dot (GQDs) coating: GQDs can be coated on the surface of KSF by physical mixing or hydrothermal coating to enhance thermal stability and luminescence intensity. However, the interaction between GQDs and the matrix is mainly weak physical adsorption, the interfacial bonding strength is insufficient, and the long-term stability is poor.
[0006] (4) Double or multiple layers of coating: such as KSF:Mn 4+ Na + @GQDs@K2SiF6, but the preparation steps are complicated, there is a lack of chemical bonding between the layers, and there are interface defects.
[0007] Therefore, there is an urgent need for a novel red phosphor and its preparation method that can synergistically improve moisture resistance, thermal stability and quantum efficiency, while also possessing simple processing, high batch consistency and strong interfacial bonding. Summary of the Invention
[0008] The purpose of this invention is to address existing problems by providing a highly stable red phosphor coated with manganese-doped potassium fluorosilicate graphene quantum dots, its preparation method, and its application.
[0009] This invention is achieved through the following technical solution: A highly stable manganese-doped potassium fluorosilicate graphene quantum dot-coated red phosphor comprises: Doped core: Na + Co-doped K 2-x Na x Sif6:Mn 4+ Grains, where x is Na + The doping mole fraction, x = 0.02~0.06, Mn 4+ The doping molar fraction is 0.01~0.02; Surface in-situ reduction passivation layer: Located on the grain surface, with a thickness of 1~5nm, it is formed by reduction treatment of ascorbic acid in a weakly acidic ethanol / water mixed medium. The Mn content in this layer... 4+ The concentration is lower than that inside the grain, and it contains Mn. 2+ / Mn 3+ ; Outer coating: A network coating layer formed by cross-linking amino / fluorine-containing bifunctional graphene quantum dots (GFQDs) with glutaraldehyde (GA). The GFQDs have a particle size of 3~6nm and the coating amount is 1.5%~3.0% of the total mass of the phosphor.
[0010] Furthermore, the F element mass fraction in the GFQDs is 1.0%~2.5%, and the N element mass fraction is 5%~10%.
[0011] Furthermore, the outer coating layer crosslinks GFQDs into a continuous network via Schiff base covalent bonds (-N=CH-); the characteristic infrared absorption peaks of the Schiff base bonds are located in the range of 1630~1650 cm⁻¹. -1 .
[0012] A method for preparing the red phosphor includes the following steps: (1) Na + Co-doped K 2-x Na x Sif6:Mn 4+ Core preparation: The silicon source, potassium source, sodium source, and manganese source are arranged according to the stoichiometric ratio K 2-x Na x Sif6:Mn 4+ Prepare the mixture; (2) Mild surface reduction passivation treatment: The powder obtained in step (1) is dispersed in a 1:1 volume ratio of ethanol / water mixed solvent with a concentration of 15~25 g / L. Ascorbic acid (L-ascorbic acid) is added, and the pH is adjusted to 5.5~6.0 with dilute ammonia. The mixture is stirred in a water bath at 40~50℃ for 20~40 min. After the reaction is completed, the mixture is centrifuged, washed 3~4 times with anhydrous ethanol, and vacuum dried at 60~65℃ for 6~12 h to obtain the surface-reduced and passivated phosphor. (3) Preparation of amino / fluorine-containing bifunctional graphene quantum dots (GFQDs): Using citric acid as the carbon source, ammonium fluoride as the fluorine source (5%~15% of the mass of citric acid), and polyethyleneimine as the amino source, GFQDs were obtained after hydrothermal reaction at 180~200℃ for 8~12h, followed by purification and drying. (4) GFQDs anchoring and GA cross-linking coating: The phosphor obtained in step (2) is dispersed in an ethanol / water mixed solvent (volume ratio (3~5):1) at a concentration of 15~25g / L and ultrasonically dispersed for 15~30min. Add the GFQDs prepared in step (3) (pre-dispersed ultrasonically in a small amount of the same mixed solvent) to the suspension, so that the dry weight of the GFQDs is 1.5% to 3.0% of the phosphor mass; Adjust the pH of the system to 7.0-7.5 with 0.1M dilute ammonia, and add glutaraldehyde aqueous solution (25wt%) under magnetic stirring. The reaction system was stirred in a water bath at 50-60℃ for 1.5-2.5 hours. After the reaction was completed, the precipitate was collected by centrifugation, washed, and then dried under vacuum at 60-65℃ for 8-12 hours to obtain the target product.
[0013] Further, in step (1), the silicon source is an aqueous solution of H2SiF6 with a concentration of 30%, the potassium source is KF, the sodium source is NaF, and the manganese source is K2MnF6.
[0014] Further, step (1) specifically involves dissolving KF and NaF in deionized water, then adding H2SiF6 and K2MnF6, and replenishing with 40% hydrofluoric acid to the total volume, so that F... - The total concentration was approximately 15 mol / L. Under constant temperature and stirring at 25–35 °C, the mixed solution was slowly added dropwise to an equal volume of ethanol to induce precipitation. After the addition was complete, stirring continued for 1–2 hours. The mixture was then filtered, and the precipitate was washed three times each with anhydrous ethanol and anhydrous diethyl ether, and then dried under vacuum at 60–65 °C for 6–12 hours to obtain K. 2-x Na x Sif6:Mn 4+ powder.
[0015] Further, the mass ratio of ascorbic acid to powder in step (2) is 1:(20~50).
[0016] Further, step (3) is specifically operated as follows: citric acid, ammonium fluoride and polyethyleneimine are dissolved in deionized water and stirred until completely dissolved. The solution is then transferred to a hydrothermal reactor lined with polytetrafluoroethylene and subjected to a hydrothermal reaction at 180~200℃ for 8~12h. After the reaction is completed, the solution is naturally cooled to room temperature and then filtered through a 0.22μm filter membrane. Large particulate impurities are removed by centrifugation at 10000~12000rpm for 15~20min. The solution is then dialyzed through a dialysis bag (with a molecular weight cutoff of 1000~3000Da) for 48~72h. Finally, the solution is vacuum dried at 60~65℃ to obtain GFQDs.
[0017] Further, in step (4), the amount of glutaraldehyde added is 1% to 3% of the mass of GFQDs; the washing includes washing with anhydrous ethanol 2 to 3 times and washing with deionized water 2 to 3 times, with a total washing time not exceeding 1 minute.
[0018] The application of the red phosphor in white LED, Mini LED or Micro LED backlight display devices.
[0019] The present invention has the following advantages over the prior art: 1. This invention utilizes Na + A three-layer gradient protection structure consisting of co-doping, ascorbic acid surface reduction passivation, and GFQDs-GA covalent crosslinking network fundamentally solves the common problems of poor moisture resistance and insufficient thermal stability in fluoride red phosphors. The inner Na... + Co-doping causes lattice shrinkage and crystal field enhancement, significantly improving thermal stability; the middle layer, formed by in-situ reduction with ascorbic acid, is Mn-poor. 4+ The passivation layer reduces the surface activity of highly active Mn. 4+ The concentration of the graphene crystals cuts off the starting point of water molecule erosion. The outer layer is a three-dimensional network composed of amino / fluorine-containing bifunctional graphene quantum dots cross-linked with glutaraldehyde Schiff base. This not only forms a dense physical waterproof barrier but also firmly anchors the GFQDs to the phosphor surface through covalent bonds, avoiding the defects of easy detachment in traditional physical adsorption. The three layers complement each other and provide progressive protection. After aging at 85℃ / 85% RH for 1000 hours, the luminescence intensity retention rate remains above 90%, and after immersion in water for 480 minutes, the retention rate is above 86%, demonstrating superior overall performance.
[0020] 2. The preparation method of this invention has a wide process window and is simple to operate. The core K... 2-x Na x Sif6:Mn 4+The antisolvent precipitation method ensures uniform nucleation and good batch consistency. Surface passivation uses ascorbic acid in an ethanol / water mixed medium, eliminating the need for strictly anhydrous conditions and avoiding the stringent low-water environment requirements of the NH4F / HCl treatment in IASP technology. The outer coating is carried out in an ethanol / water solvent, utilizing an appropriate amount of water to promote the Schiff base reaction. At the same time, the high ethanol ratio protects the phosphor from hydrolysis, eliminating the need for inert gas protection. Furthermore, the washing step mainly uses anhydrous ethanol, significantly reducing the risk of phosphor degradation upon contact with water. Attached Figure Description
[0021] Figure 1 The comparison results show the quantum efficiency of each embodiment and comparative example; Figure 2 The results show the comparison of retention rates of each embodiment and comparative example after aging at 85°C / 85% RH for 1000 hours. Figure 3 The results show the comparison of retention rates after 480 minutes of water immersion in each embodiment and comparative example. Figure 4 The results show the comparison of the relative strength of each embodiment and comparative example at 150°C. Detailed Implementation
[0022] To further explain the present invention, the following specific embodiments are described.
[0023] Example 1 A method for preparing red phosphor coated with highly stable manganese-doped potassium fluorosilicate graphene quantum dots includes the following steps: (1) Na + Co-doped K 2-x Na x Sif6:Mn 4+ Core preparation: The silicon source (H2SiF6 aqueous solution, concentration 30%), potassium source (KF), sodium source (NaF), and manganese source (K2MnF6) were mixed according to the stoichiometric ratio K... 2-x Na x Sif6:Mn 4+ Prepare the mixture; The specific procedure is as follows: Dissolve KF and NaF in deionized water, then add H2SiF6 and K2MnF6, and add 40% hydrofluoric acid to the total volume to make F - The total concentration was approximately 15 mol / L. Under constant temperature stirring at 25°C, the mixed solution was slowly added dropwise to an equal volume of ethanol to induce precipitation. After the addition was complete, stirring continued for 2 hours. The mixture was then filtered, and the precipitate was washed three times each with anhydrous ethanol and anhydrous diethyl ether, and then dried under vacuum at 60°C for 12 hours to obtain K. 2-x Na x Sif6:Mn 4+powder; (2) Mild surface reduction passivation treatment: The powder obtained in step (1) was dispersed in a 1:1 volume ratio of ethanol / water mixed solvent with a concentration of 15 g / L. Ascorbic acid (L-ascorbic acid) was added, and the mass ratio of ascorbic acid to powder was 1:20. The pH was adjusted to 5.5 with dilute ammonia water. The mixture was stirred in a 40°C water bath for 40 min. After the reaction was completed, the mixture was centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 60°C for 12 h to obtain a surface-reduced and passivated phosphor. (3) Preparation of amino / fluorine-containing bifunctional graphene quantum dots (GFQDs): Using citric acid as the carbon source, ammonium fluoride as the fluorine source (5% of the mass of citric acid), and polyethyleneimine as the amino source, GFQDs were obtained after hydrothermal reaction at 180℃ for 12 hours, followed by purification and drying. The specific operation is as follows: Citric acid, ammonium fluoride and polyethyleneimine are dissolved in deionized water and stirred until completely dissolved. The solution is then transferred to a hydrothermal reactor lined with polytetrafluoroethylene and subjected to a hydrothermal reaction at 180°C for 12 hours. After the reaction is completed, the solution is naturally cooled to room temperature and then filtered through a 0.22 μm filter membrane. Large particulate impurities are removed by centrifugation at 10,000 rpm for 20 minutes. The solution is then dialyzed through a dialysis bag (with a molecular weight cutoff of 1000~3000 Da) for 48 hours. Finally, the solution is vacuum dried at 60°C to obtain GFQDs. (4) GFQDs anchoring and GA cross-linking coating: The phosphor obtained in step (2) was dispersed in an ethanol / water mixed solvent (volume ratio 3:1) at a concentration of 15 g / L and ultrasonically dispersed for 15 min. Add the GFQDs prepared in step (3) (pre-dispersed ultrasonically in a small amount of the same mixed solvent) to the suspension so that the dry weight of the GFQDs is 1.5% of the mass of the phosphor; Adjust the pH of the system to 7.0 with 0.1M dilute ammonia solution. Under magnetic stirring, add glutaraldehyde aqueous solution (25wt%), the amount of glutaraldehyde added being 1% of the mass of GFQDs. The washing process includes two washes with anhydrous ethanol and two rapid washes with deionized water, with a total washing time not exceeding 1 minute. The reaction system was stirred in a 50℃ water bath for 2.5 h. After the reaction was completed, the precipitate was collected by centrifugation, washed twice with anhydrous ethanol and deionized water, and then dried under vacuum at 60℃ for 12 h to obtain the target product.
[0024] Example 2 A method for preparing red phosphor coated with highly stable manganese-doped potassium fluorosilicate graphene quantum dots includes the following steps: (1) Na + Co-doped K 2-x Nax Sif6:Mn 4+ Core preparation: The silicon source (H2SiF6 aqueous solution, concentration 30%), potassium source (KF), sodium source (NaF), and manganese source (K2MnF6) were mixed according to the stoichiometric ratio K... 2-x Na x Sif6:Mn 4+ Prepare the mixture; The specific procedure is as follows: Dissolve KF and NaF in deionized water, then add H2SiF6 and K2MnF6, and add 40% hydrofluoric acid to the total volume to make F - The total concentration was approximately 15 mol / L. Under constant temperature stirring at 30℃, the mixed solution was slowly added dropwise to an equal volume of ethanol to induce precipitation. After the addition was complete, stirring continued for 1.5 h. The mixture was then filtered, and the precipitate was washed three times each with anhydrous ethanol and anhydrous diethyl ether, and then dried under vacuum at 62℃ for 9 h to obtain K. 2-x Na x Sif6:Mn 4+ powder; (2) Mild surface reduction passivation treatment: The powder obtained in step (1) was dispersed in a 1:1 volume ratio of ethanol / water mixed solvent with a concentration of 20 g / L. Ascorbic acid (L-ascorbic acid) was added, and the mass ratio of ascorbic acid to powder was 1:35. The pH was adjusted to 5.8 with dilute ammonia water. The mixture was stirred in a 45°C water bath for 30 min. After the reaction was completed, the mixture was centrifuged, washed three times with anhydrous ethanol, and vacuum dried at 62°C for 9 h to obtain a surface-reduced and passivated phosphor. (3) Preparation of amino / fluorine-containing bifunctional graphene quantum dots (GFQDs): Using citric acid as the carbon source, ammonium fluoride as the fluorine source (10% of the mass of citric acid), and polyethyleneimine as the amino source, GFQDs were obtained after hydrothermal reaction at 190℃ for 10 h, followed by purification and drying. The specific operation is as follows: Citric acid, ammonium fluoride and polyethyleneimine are dissolved in deionized water and stirred until completely dissolved. The solution is then transferred to a hydrothermal reactor lined with polytetrafluoroethylene and subjected to a hydrothermal reaction at 190°C for 10 hours. After the reaction is completed, the solution is naturally cooled to room temperature and then filtered through a 0.22 μm filter membrane. Large particulate impurities are removed by centrifugation at 11,000 rpm for 18 minutes. The solution is then dialyzed through a dialysis bag (with a molecular weight cutoff of 1000~3000 Da) for 55 hours and finally dried under vacuum at 62°C to obtain GFQDs. (4) GFQDs anchoring and GA cross-linking coating: The phosphor obtained in step (2) was dispersed in an ethanol / water mixed solvent (volume ratio 4:1) at a concentration of 20 g / L and ultrasonically dispersed for 25 min. Add the GFQDs prepared in step (3) (pre-dispersed ultrasonically in a small amount of the same mixed solvent) to the suspension so that the dry weight of the GFQDs is 2.0% of the phosphor mass; Adjust the pH of the system to 7.2 with 0.1M dilute ammonia solution. Under magnetic stirring, add 25wt% glutaraldehyde aqueous solution, the amount of glutaraldehyde added being 2% of the mass of GFQDs. The washing process includes two washes with anhydrous ethanol and two rapid washes with deionized water, with a total washing time not exceeding 1 minute. The reaction system was stirred in a 55℃ water bath for 2 hours. After the reaction was completed, the precipitate was collected by centrifugation, washed twice with anhydrous ethanol and deionized water, and then dried under vacuum at 62℃ for 10 hours to obtain the target product.
[0025] Example 3 A method for preparing red phosphor coated with highly stable manganese-doped potassium fluorosilicate graphene quantum dots includes the following steps: (1) Na + Co-doped K 2-x Na x Sif6:Mn 4+ Core preparation: The silicon source (H2SiF6 aqueous solution, concentration 30%), potassium source (KF), sodium source (NaF), and manganese source (K2MnF6) were mixed according to the stoichiometric ratio K... 2-x Na x Sif6:Mn 4+ Prepare the mixture; The specific procedure is as follows: Dissolve KF and NaF in deionized water, then add H2SiF6 and K2MnF6, and add 40% hydrofluoric acid to the total volume to make F - The total concentration was approximately 15 mol / L. Under constant temperature stirring at 35°C, the mixed solution was slowly added dropwise to an equal volume of ethanol to induce precipitation. After the addition was complete, stirring continued for 1 hour. The mixture was then filtered, and the precipitate was washed three times each with anhydrous ethanol and anhydrous diethyl ether, and then dried under vacuum at 65°C for 6 hours to obtain K. 2-x Na x Sif6:Mn 4+ powder; (2) Mild surface reduction passivation treatment: The powder obtained in step (1) was dispersed in a 1:1 volume ratio of ethanol / water mixed solvent with a concentration of 25 g / L. Ascorbic acid (L-ascorbic acid) was added, and the mass ratio of ascorbic acid to powder was 1:50. The pH was adjusted to 6.0 with dilute ammonia water. The mixture was stirred in a 50°C water bath for 20 min. After the reaction was completed, the mixture was centrifuged, washed 4 times with anhydrous ethanol, and vacuum dried at 65°C for 6 h to obtain a surface-reduced and passivated phosphor. (3) Preparation of amino / fluorine-containing bifunctional graphene quantum dots (GFQDs): Using citric acid as the carbon source, ammonium fluoride as the fluorine source (15% of the mass of citric acid), and polyethyleneimine as the amino source, GFQDs were obtained after hydrothermal reaction at 200℃ for 8 hours, followed by purification and drying. The specific operation is as follows: Citric acid, ammonium fluoride and polyethyleneimine are dissolved in deionized water and stirred until completely dissolved. The solution is then transferred to a hydrothermal reactor lined with polytetrafluoroethylene and subjected to a hydrothermal reaction at 200°C for 8 hours. After the reaction is completed, the solution is naturally cooled to room temperature and then filtered through a 0.22 μm filter membrane. Large particulate impurities are removed by centrifugation at 12,000 rpm for 15 minutes. The solution is then dialyzed through a dialysis bag (with a molecular weight cutoff of 1,000~3,000 Da) for 72 hours. Finally, the solution is vacuum dried at 65°C to obtain GFQDs. (4) GFQDs anchoring and GA cross-linking coating: The phosphor obtained in step (2) was dispersed in an ethanol / water mixed solvent (volume ratio 5:1) at a concentration of 25 g / L and ultrasonically dispersed for 15 min. Add the GFQDs prepared in step (3) (pre-dispersed ultrasonically in a small amount of the same mixed solvent) to the suspension so that the dry weight of the GFQDs is 3.0% of the mass of the phosphor; Adjust the pH of the system to 7.5 with 0.1M dilute ammonia water, and add glutaraldehyde aqueous solution (25wt%) under magnetic stirring. The amount of glutaraldehyde added is 3% of the mass of GFQDs. The washing includes washing 3 times with anhydrous ethanol and washing 3 times with deionized water. The total washing time does not exceed 1 minute. The reaction system was stirred in a 60℃ water bath for 1.5 h. After the reaction was completed, the precipitate was collected by centrifugation, washed three times with anhydrous ethanol and deionized water, and then dried under vacuum at 65℃ for 8 h to obtain the target product.
[0026] Comparative Example 1 Compared with Example 2, this Comparative Example 1 omits step (2), that is, the powder obtained in step (1) directly enters the coating in step (4), and the other conditions are the same as those in Example 2.
[0027] Comparative Example 2 Compared with Example 2, Comparative Example 2 does not include the addition of glutaraldehyde in step (4), while the other conditions are the same as in Example 2.
[0028] Comparative Example 3 Compared with Example 2, the solvent in step (4) of Comparative Example 3 was replaced with anhydrous ethanol (water-free), and the other conditions were the same as those in Example 2.
[0029] Comparative Example 4 Compared with Example 2, Comparative Example 4 does not include NaF in step (1), i.e., K2SiF6:Mn is synthesized. 4+ (Mn) 4+ The concentration is the same as in Example 2. Other steps are the same as in Example 2.
[0030] Experimental Test 1. Internal quantum efficiency (IQE) test An Edinburgh FL S1000 fluorescence spectrometer equipped with an integrating sphere was used. The laser wavelength was 450 nm and the slit width was 2 nm. The phosphor sample was placed in the integrating sphere, and the scattering spectrum before the excitation light entered the sample and the scattering and emission spectra after the excitation light entered the sample were measured. The IQE was calculated according to the following formula: Each sample was tested three times and the average value was taken.
[0031] Test results are as follows Figure 1 As shown, by Figure 1 It can be seen that the internal quantum efficiency (IQE) of all three embodiments remains above 91%, with Embodiment 1 showing the highest IQE. As the coating thickness increases from 1.5% to 3.0%, the IQE exhibits a slight decreasing trend. This is because the thicker GFQD network layer causes some scattering and absorption of the incident excitation light and the emitted light. However, even with a coating thickness of 3.0%, the IQE remains above 91%, indicating that GFQDs have good optical transparency and minimal negative impact on luminescence efficiency. Comparative Embodiment 4 has the lowest IQE, confirming that Na… + Doping can optimize the lattice field environment and increase the probability of radiative transitions. The IQE of Comparative Example 1 and Comparative Example 3 were 90.8% and 92.5%, respectively, which were close to those of Example 2, indicating that surface defects and the cross-linking state of the coating layer had little impact on quantum efficiency. The IQE of Comparative Example 3 was 88.4%, which was due to some light loss caused by uneven coating.
[0032] 2. Aging test at 85℃ / 85% RH The phosphor sample (0.5g per portion) was evenly spread in a glass petri dish and placed in a constant temperature and humidity chamber (ESPEC AR-2000) at 85℃ and 85% relative humidity. Every 100 hours, a small amount of sample was taken out, cooled to room temperature in a desiccator, and then the luminescence intensity was measured (450nm excitation, 630nm emission monitoring). With the initial luminescence intensity as 100%, the retention rate at different aging times was calculated, and the test was conducted up to 1000 hours.
[0033] Note: Comparative Example 1 had a strength retention rate of less than 60% after 500h, so the test was not continued to 1000h.
[0034] Test results are as follows Figure 2 As shown, by Figure 2It can be seen that the luminescence intensity retention rate of all three examples exceeded 90% after 1000 hours of aging. In contrast, the retention rate of the comparative example was only 52.1% after 1500 hours, and could not be measured after 1000 hours. This indicates that Mn 4+ The high activity of the phosphor is the starting point for hydrolysis. Unpassivated phosphors rapidly degrade in humid and hot environments. Comparative Example 2 demonstrates that ascorbic acid reduction leads to Mn deficiency. 4+ The aging retention rate of Comparative Example 2 is significantly lower than that of Example 2, reaching only 78.6% after 1000 hours. The uncovalently crosslinked GFQDs layer gradually detaches in a humid and hot environment, resulting in a loss of protective function. The aging retention rate of Comparative Example 3 is 73.5%, also inferior to Example 2. The Schiff base reaction in pure ethanol failed to occur effectively, preventing the GFQDs from forming a robust network. The aging retention rate of Comparative Example 4 is 86.2%, slightly lower than that of Example 2, indicating that Na… + Doping indirectly improves moisture resistance by reducing lattice defects.
[0035] 3. Water immersion test Take 0.1 g of phosphor sample and disperse it in 10 mL of deionized water (25℃). Stir magnetically (200 rpm). Take samples at 120 min, 240 min, 360 min, and 480 min, centrifuge, vacuum dry, and test the luminescence intensity. Calculate the retention rate with the luminescence intensity of the unimpregnated sample as 100%.
[0036] Note: Comparative Example 1 was already below 50% after immersion in water for 240 minutes, so it was not tested up to 480 minutes.
[0037] Test results are as follows Figure 3 As shown, by Figure 3 It can be seen that the luminescence intensity retention rate of all three examples was higher than 86% after immersion in water for 480 minutes, consistent with the trend of the aging test. The higher the coating amount, the more complete the cross-linking, and the better the waterproof effect. In Comparative Example 1, the retention rate dropped to 34.5% after immersion in water for 240 minutes, and could not be measured after 480 minutes. The exposed Mn on the KSF surface... 4+ It reacts rapidly with water, causing luminescence quenching. Comparative Example 2 showed a retention rate of 65.2% after 480 minutes of water immersion, significantly lower than Example 2. Comparative Example 3 showed a retention rate of 71.3%, between Comparative Example 2 and Example 2. Comparative Example 4 showed a retention rate of 84.7%, slightly lower than Example 2. The water immersion test results are highly consistent with the high-temperature and high-humidity aging test results, further verifying the effectiveness of the three-layer protection strategy of this invention.
[0038] 4. Thermal quenching test A fluorescence spectrometer (Hitachi F-7000 with TAP-02 heating stage) equipped with a heating stage was used, with an excitation wavelength of 450 nm and emission at 630 nm monitored. The sample was heated from 30 °C to 200 °C at a heating rate of 5 °C / min, and the luminescence intensity was recorded every 10 °C. The relative intensity at each temperature was calculated with the luminescence intensity at 30 °C as 100%.
[0039] Test results are as follows Figure 4 As shown, by Figure 4 It can be seen that the luminescence intensity of all three examples at 150℃ is close to or exceeds the room temperature intensity, indicating that the phosphor of the present invention hardly undergoes thermal quenching at 150℃. Comparative Example 4 shows a significant decrease in thermal stability, with a relative intensity of only 83.9% at 150℃, directly proving that Na... + Co-doping plays a key role in improving thermal stability, Na + Replace part of K + Afterwards, the lattice contracts, and Mn 4+ The surrounding crystal field is enhanced, and nonradiative transitions are effectively suppressed. Comparative Example 1 has a yield of 94.2%, Comparative Example 2 has a yield of 96.8%, and Comparative Example 3 has a yield of 93.5%, all slightly lower than that of Example 2, indicating that surface passivation and a complete coating layer also have a certain auxiliary effect on thermal stability.
[0040] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A highly stable red phosphor coated with manganese-doped potassium fluorosilicate graphene quantum dots, characterized in that, include: Doped core: Na + Co-doped K 2-x Na x Sif6:Mn 4+ Grains, where x is Na + The doping mole fraction, x = 0.02~0.06, Mn 4+ The doping molar fraction is 0.01~0.02; Surface in-situ reduction passivation layer: Located on the grain surface, with a thickness of 1~5nm, it is formed by reduction treatment of ascorbic acid in a weakly acidic ethanol / water mixed medium. The Mn content in this layer... 4+ The concentration is lower than that inside the grain, and it contains Mn. 2+ / Mn 3+ ; Outer coating: A network coating layer formed by cross-linking amino / fluorine-containing bifunctional graphene quantum dots (GFQDs) with glutaraldehyde. The GFQDs have a particle size of 3-6 nm and the coating amount is 1.5%-3.0% of the total mass of the phosphor.
2. The phosphor according to claim 1, characterized in that, The F element mass fraction in the GFQDs is 1.0%~2.5%, and the N element mass fraction is 5%~10%.
3. The phosphor according to claim 1, characterized in that, The outer coating layer crosslinks GFQDs into a continuous network via Schiff base covalent bonds -N=CH-.
4. A method for preparing the red phosphor of claim 1, characterized in that, Includes the following steps: (1) Na + Co-doped K 2-x Na x Sif6:Mn 4+ Core preparation: The silicon source, potassium source, sodium source, and manganese source are arranged according to the stoichiometric ratio K 2-x Na x Sif6:Mn 4+ Prepare the mixture; (2) Mild surface reduction passivation treatment: The powder obtained in step (1) is dispersed in an ethanol / water mixed solvent with a concentration of 15~25g / L. Ascorbic acid is added, and the pH is adjusted to 5.5~6.0 with dilute ammonia. The mixture is stirred in a water bath at 40~50℃ for 20~40min. After the reaction is completed, the mixture is centrifuged, washed 3~4 times with anhydrous ethanol, and vacuum dried at 60~65℃ for 6~12h to obtain a surface-reduced and passivated phosphor. (3) Preparation of amino / fluorine-containing bifunctional graphene quantum dots (GFQDs): Using citric acid as the carbon source, ammonium fluoride as the fluorine source, and polyethyleneimine as the amino source, GFQDs were obtained after hydrothermal reaction at 180-200℃ for 8-12 hours, followed by purification and drying. (4) GFQDs anchoring and GA cross-linking coating: The phosphor obtained in step (2) is dispersed in an ethanol / water mixed solvent at a concentration of 15~25g / L and ultrasonically dispersed for 15~30min; Add the GFQDs prepared in step (3) to the suspension so that the dry weight of the GFQDs is 1.5% to 3.0% of the phosphor mass; Adjust the pH of the system to 7.0-7.5 with 0.1M dilute ammonia solution, and add glutaraldehyde aqueous solution under magnetic stirring; The reaction system was stirred in a water bath at 50-60℃ for 1.5-2.5 hours. After the reaction was completed, the precipitate was collected by centrifugation, washed, and then dried under vacuum at 60-65℃ for 8-12 hours to obtain the target product.
5. The method according to claim 4, characterized in that, The silicon source mentioned in step (1) is an aqueous solution of H2SiF6 with a concentration of 30%, the potassium source is KF, the sodium source is NaF, and the manganese source is K2MnF6.
6. The method according to claim 4, characterized in that, Step (1) involves dissolving KF and NaF in deionized water, then adding H2SiF6 and K2MnF6; under constant temperature stirring at 25-35℃, adding the mixed solution dropwise to an equal volume of ethanol to induce precipitation; after the addition is complete, continue stirring for 1-2 hours, filter, and wash the precipitate three times each with anhydrous ethanol and anhydrous diethyl ether, then vacuum dry at 60-65℃ for 6-12 hours to obtain KF. 2-x Na x Sif6:Mn 4+ powder.
7. The method according to claim 4, characterized in that, The mass ratio of ascorbic acid to powder in step (2) is 1:(20~50).
8. The method according to claim 4, characterized in that, Step (3) is as follows: Citric acid, ammonium fluoride and polyethyleneimine are dissolved in deionized water and stirred until completely dissolved. The solution is then transferred to a hydrothermal reactor lined with polytetrafluoroethylene and subjected to a hydrothermal reaction at 180-200℃ for 8-12 hours. After the reaction is completed, the solution is naturally cooled to room temperature and then filtered through a 0.22μm filter membrane. Large particulate impurities are removed by centrifugation at 10000-12000rpm for 15-20 minutes. The solution is then dialyzed through a dialysis bag for 48-72 hours and finally vacuum dried at 60-65℃ to obtain GFQDs.
9. The method according to claim 4, characterized in that, In step (4), the amount of glutaraldehyde added is 1% to 3% of the mass of GFQDs; the washing includes washing with anhydrous ethanol 2 to 3 times and washing with deionized water 2 to 3 times, with a total washing time not exceeding 1 minute.
10. The application of the red phosphor according to claim 1 in white LED, Mini LED or Micro LED backlight display devices.